ASPEK DEMOKRASI PEMBENTUKAN PERATURAN DAERAH DALAM PERSPEKTIF SOCIO-LEGAL - Rodiyah Rodiyah (Masalah-Masalah Hukum, 2012)
The state must be built from two concepts that is law and democracy. Paradigm shift in constitutional law in the amendment to the 1945 democratic consequences formation process of legislation, including regulation. This means that its formation must meet the normative dimension of democracy and sociological material. Normative dimension Stufenbautheory analyzed in accordance with Law No.10 of 2004, Law No.23 of 2004 and Permendagri No. 16 of 2006. Material dimension of democracy sociological perspective can be analyzed with the legal workings Chambliss, Seidman, Selznick and responsive Nonet-Habermas's Communication Theory of Justice. Establishment of Legislation in the form of regulation is formed by using analysis Talcot Parsons on cybernetic patterns of socio-cultural sub-systems in the aspect of democracy.Keywords : Law democracy, sociological material, responsive